Heightened Complement Sensitivity of Acquired Immunodeficiency Syndrome Lymphocytes Related to Diminished Expression of Decay-Accelerating Factor - Lederman, Michael M.; Purvis, Scott F.; Walter, Elizabeth I.; Carey, John T.; Medof, M. Edward (Proceedings of the National Academy of Sciences - PNAS, 1989)
Although the human immunodeficiency virus can induce cytopathic changes in human lymphocytes in vitro, the mechanism(s) underlying progressive lymphopenia in patients with AIDS and AIDS-related complex has not been elucidated. To investigate this issue, peripheral blood lymphocytes of AIDS and AIDS-related complex patients and healthy control subjects were examined for their ability to resist homologous complement-mediated lysis. Upon sensitization with monoclonal antibodies to major histocompatibility complex class I antigen, as much as 48% lysis of patients' cells was observed in as little as a 1:32 dilution of human serum compared to 18 ± 8% (mean ± SD) lysis of controls' cells even in a 1:8 dilution of human serum. To investigate the mechanism of the abnormal complement sensitivity, AIDS and AIDS-related complex cells were analyzed for expression of decay-accelerating factor (DAF), a complement regulatory protein that functions intrinsically in blood cell membranes to prevent complement activation on their surfaces. Flow cytometric assays using anti-DAF monoclonal antibodies demonstrated that patients' lymphocytes and monocytes were DAF-deficient, in contrast to their polymorphonuclear leukocytes, which showed normal DAF levels. Expression of DAF was diminished on CD4+as well as CD8+T-lymphocyte subpopulations as opposed to expression of CD3, which was comparable in patients and controls. Incubation of normal lymphocytes with anti-DAF monoclonal antibodies or phosphatidylinositol-specific phospholipase C, an enzyme that cleaves DAF, enhanced lysis. Conversely, reconstitution of patients' cells with exogenous DAF reduced their lysis. The findings of heightened complement sensitivity and DAF deficiency of patients' lymphocytes in vitro suggest the possibility that the DAF deficit may contribute to the progressive lymphopenia of AIDS in vivo.